Prevention of Hypomineralization In Auditory Ossicles of Vitamin D Receptor (Vdr) Deficient Mice - Delsmann, Maximilian M.; Peichl, Jonathan; Yorgan, Timur A.; Beil, Frank Timo; Amling, Michael; Demay, Marie B.; Rolvien, Tim (Frontiers in Endocrinology, 2022)
Intact mineralization of the auditory ossicles - the smallest bones in the body - is essential for sound transmission in the middle ear, while ossicular hypomineralization is associated with conductive hearing loss. Here, we performed a high-resolution analysis of the ossicles in vitamin D receptor deficient mice (Vdr-/-), which are characterized by hypocalcemia and skeletal mineralization defects, and investigated whether local hypomineralization can be prevented by feeding a calcium-rich rescue diet (Vdr-/- res). In Vdr-/- mice fed a regular diet (Vdr-/- reg), quantitative backscattered electron imaging (qBEI) revealed an increased void volume (porosity, p<0.0001) along with lower mean calcium content (CaMean, p=0.0008) and higher heterogeneity of mineralization (CaWidth, p=0.003) compared to WT mice. Furthermore, a higher osteoid volume per bone volume (OV/BV; p=0.0002) and a higher osteocyte lacunar area (Lc.Ar; p=0.01) were found in histomorphometric analysis in Vdr-/- reg mice. In Vdr-/- res mice, full rescue of OV/BV and Lc.Ar (both p>0.05 vs. WT) and partial rescue of porosity and CaWidth (p=0.02 and p=0.04 vs. WT) were observed. Compared with Hyp mice, a model of X-linked hypophosphatemic rickets, Vdr-/- reg mice showed a lower osteoid volume in the ossicles (p=0.0002), but similar values in the lumbar spine. These results are consistent with later postnatal impairment of mineral homeostasis in Vdr-/- mice than in Hyp mice, underscoring the importance of intact mineral homeostasis for ossicle mineralization during development. In conclusion, we revealed a distinct phenotype of hypomineralization in the auditory ossicles of Vdr-/- mice that can be partially prevented by a rescue diet. Since a positive effect of a calcium-rich diet on ossicular mineralization was demonstrated, our results open new treatment strategies for conductive hearing loss. Future studies should investigate the impact of improved ossicular mineralization on hearing function.